If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (Y) * 6 + 24 + -2 = 14 Reorder the terms for easier multiplication: 6Y + 24 + -2 = 14 Reorder the terms: 24 + -2 + 6Y = 14 Combine like terms: 24 + -2 = 22 22 + 6Y = 14 Solving 22 + 6Y = 14 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 6Y = 14 + -22 Combine like terms: 22 + -22 = 0 0 + 6Y = 14 + -22 6Y = 14 + -22 Combine like terms: 14 + -22 = -8 6Y = -8 Divide each side by '6'. Y = -1.333333333 Simplifying Y = -1.333333333
| 13+x/20-5x/2=10+x/5+1-12x/10 | | x/2+x-3/8+2x+2/16=x-2/2 | | 1/33.146 | | 3x^2-2X^2+x^3+4-X^2+4x-2-x= | | x/3+x/9-4x/27=11/27-x/9 | | (3x/15)-x=-(3x/3)+(9/5) | | 3x/15-x=-3x/3+9/5 | | H/4=(H+12)/12 | | 4/7=n/5.4 | | 12/72=n/9 | | 2x+18y=14 | | x=-9y+7 | | (3r-8)(2r-7)=0 | | 5-3(b+2)=(2b+7)-(b-2) | | (n+4)*10=80 | | (2+7f)(3-8f)=0 | | 3Xx=2 | | 3x+11=-33+-8x | | x^4+7x^2+10x-1=0 | | 20=7c-1 | | 41-4x=5x+18 | | 5x+8y=7x-3y | | 10x+15=6x+95 | | x+9=-89-8x | | 7x-(4-3x)=5+(3x-1) | | 5+3(2x+2)=6+4(x+1) | | 15=6x^2-23x-15 | | 3+4x+8x=15 | | (2x+3)+(x-7)=5x-(3x-7) | | (2x-2)+3x=128 | | (2x-2)+3x=2 | | 2x+123=5 |